The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13013-016-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

The paradoxical relationship between ligamentum flavum hypertrophy and developmental lumbar spinal stenosis

Abstract: BackgroundLigamentum flavum (LF) hypertrophy is a common cause of lumbar spinal stenosis and is thought to be degeneration-driven. Developmental spinal stenosis (DSS) is characterized by pre-existing narrowed spinal canals and is likely a developmental problem that occurs in childhood. In these cases, the LF may demonstrate different characteristics as compared to degeneration-driven stenosis. Thus, this study aimed to investigate the relationship between histological changes of LF and canal size.MethodsPatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
15
2
Order By: Relevance
“…Predisposing factors of symptomatic DSS includes degeneration of intervertebral discs, facet joints, or the ligamentum flavum. 1,11,20,23,41 Some genetic factors have been implicated in the etiology of lumbar spinal degeneration. 36,37,[42][43][44] There is likely a direct correlation between spinal stenosis and disc degeneration because these two pathologies usually coexist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predisposing factors of symptomatic DSS includes degeneration of intervertebral discs, facet joints, or the ligamentum flavum. 1,11,20,23,41 Some genetic factors have been implicated in the etiology of lumbar spinal degeneration. 36,37,[42][43][44] There is likely a direct correlation between spinal stenosis and disc degeneration because these two pathologies usually coexist.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes in DSS include narrowing of the dorsal aspect of the spinal canal due to bulging of the inferior articular facets. A paradoxical relationship with the degree of ligamentum flavum fibrosis has also been observed . The lamina is also enlarged with narrowed interlaminar spaces and the pedicles are also shortened leading to decreased interpedicular distances .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…One must appreciate the unique pathological characteristics of DSS that distinguish it from degenerative/acquired lumbar spinal stenosis. Previous studies have characterized DSS with both x‐ray and magnetic resonance imaging (MRI) phenotyping, having a paradoxical relationship with ligamentum flavum hypertrophy, and possible genetic origins . Yet, further understanding of its pathophysiology is necessary to determine the clinical significance of DSS.…”
mentioning
confidence: 99%
“…There are several pathogenic factors that lead to LSS, such as disc degeneration, facet degeneration, and hypertrophy of the ligamentum flavum (HLF) [6]. Among these pathogenic factors, HLF plays a vital role in LSS [7][8][9][10]. Previous studies have indicated that fibrosis of the ligamentum flavum stimulated by chronic inflammation is considered to be the most important pathological process of HLF [11,12].…”
Section: Introductionmentioning
confidence: 99%